Anomia coercitiva para comparecencia del procesado en juzgamiento en materia penal por daños materiales - López Macías, Danny Eddy (2025)
The accusatory criminal process is a legal system in which the formal accusation is made by the State Attorney General's Office, while the defense of the accused is handled by their legal representative. Its main goal is to ensure an impartial and fair trial, grounded in the guarantees of due process. However, a significant issue arises due to the absence of a coercive rule that mandates the accused to attend the trial hearing in cases of material damages. Consequently, this study aims to theoretically and legally examine how the lack of a coercive mechanism for ensuring the accused's attendance at trial hearings in traffic cases involving material damages contributes to impunity in these offenses. This scientific article adopts a mixed-method approach, combining both quantitative and qualitative methods within a non-experimental, cross-sectional research design, with a descriptive, explanatory, and legal-dogmatic scope. The research will utilize analytical-synthetic, inductive-deductive, and historical-logical methods, along with techniques such as surveys, interviews, and content analysis. The findings of the research concluded that the repeated absence of the accused at the trial hearing can cause severe harm to the victim and the judicial process as a whole, leading to delays, complicating the presentation of evidence, and causing frustration and distress to the victim. It is crucial to implement effective measures to ensure the accused's attendance and protect the victim's rights in these cases, including penalties for noncompliance and reforms to the legal framework.